Software engineer's pocket book - Tooley, Michael M. (Newnes, 1994)
Software Engineer's Pocket Book provides a concise discussion on various aspects of software engineering. The book is comprised of six chapters that tackle various areas of concerns in software engineering. Chapter 1 discusses software development, and Chapter 2 covers programming languages. Chapter 3 deals with operating systems. The book also tackles discrete mathematics and numerical computation. Data structures and algorithms are also explained. The text will be of great use to individuals involved in the specification, design, development, implementation, testing, maintenance, and qualit.